Determinants for Sensitivity of Human Immunodeficiency Virus Coreceptor CXCR4 to the Bicyclam AMD3100 - Labrosse, Béatrice (American Society for Microbiology, 1998)
The bicyclam AMD3100 is a potent and selective inhibitor of the replication of human immunodeficiency virus type 1 and type 2 (HIV-1 and HIV-2). It was recently demonstrated that the compound inhibited HIV entry through CXCR4 but not through CCR5. Selectivity of AMD3100 for CXCR4 was further indicated by its lack of effect on HIV-1 and HIV-2 infection mediated by the CCR5, CCR3, Bonzo, BOB, and US28, coreceptors. AMD3100 completely blocked HIV-1 infection mediated by a mutant CXCR4 bearing a deletion of most of the amino-terminal extracellular domain. In contrast, relative resistance to AMD3100 was conferred by different single amino acid substitutions in the second extracellular loop (ECL2) or in the adjacent membrane-spanning domain, TM4. Only substitutions of a neutral residue for aspartic acid and of a nonaromatic residue for phenylalanine (Phe) were associated with drug resistance. This suggests a direct interaction of AMD3100 with these amino acids rather than indirect effects of their mutation on the CXCR4 structure. The interaction of aspartic acids of ECL2 and TM4 with AMD3100 is consistent with the positive charge of bicyclams, which might block HIV-1 entry by preventing electrostatic interactions between CXCR4 and the HIV-1 envelope protein gp120. Other features of AMD3100 must account for its high antiviral activity, in particular the presence of an aromatic linker between the cyclam units. This aromatic group might engage in hydrophobic interactions with the Phe-X-Phe motifs of ECL2 or TM4. These results confirm the importance of ECL2 for the HIV coreceptor activity of CXCR4.